Knowledge, perception and willingness of mothers to accept malaria vaccine for their children in Ondo West Local Government, Ondo State - Andrew, Oluwafisayo Deborah (Discover Public Health, 2025)
Significant stride has been made to control malaria in the past. Recently malaria vaccine was developed as a control measure for malaria. However, previous vaccination programmes in Nigeria has faced issue with high rate of hesitancy. This study therefore assessed the knowledge, perception and willingness of mothers to accept malaria vaccines for their children prior to its availability for use.